Efektivitas Pengelolaan BUMDes dalam Meningkatkan Perekonomian Masyarakat: Studi Kasus di Desa Puuroda - Hidayat, Rahmat; Amalia, Dea Rizky; Fitria, Dian (CV. Social Politic Genius (SIGn), 2024)
This study aims to analyze the effectiveness of Karya Bakti’s management in enhancing the community economy in Puuroda Village. Karya Bakti operates three main programs: Agricultural Land Financing, provision of Agricultural Production Facilities, and Goods Transportation Rental Services. This research employs a descriptive qualitative approach with data collection techniques through participatory observation, in-depth interviews, and documentation studies. Research informants were selected using purposive sampling. Data analysis was performed using Miles and Huberman’s interactive model. The results show that Karya Bakti has not been fully effective based on Campbell’s five performance indicators: Program Success, Goal Attainment, Program Satisfaction, Input and Output Levels, and Overall Goal Achievement. Program socialization has not been optimal, sales and utilization targets for several programs have not been achieved, and the level of community satisfaction is low. In addition, the management of the VOE is not yet efficient, and the Overall Goal Achievement in improving community welfare has not been significant. Transparency and accountability are also inhibiting factors. It is concluded that Karya Bakti has not been optimal in carrying out its function as a driver of the village economy.